Sedimentation of refined cellulosic pulp fines in the suspension during physical agglomeration - Nikolai Voinov; Anastasiya Bogatkova; Denis Zemtsov; Aleksandr Vititnev; Roman Marchenko (BioResources)
A physical coagulator of fines was employed to separate suspensions comprising refined sulphate cellulose and waste paper, where no reagents were required. The physical coagulator was a porous cylinder with a rotating disk placed in its cavity. Using the MorFi Neo fibre analyser and the Hitachi SU 3500 digital microscope, a dispersed size distribution of well-developed fines in a suspension derived from softwood and hardwood pulp was obtained. The kinetics of fine sedimentation in the suspension was studied. The sedimentation rate of both individual agglomerates and a mass of them, as well as the magnitude of mass concentration in a cleared liquid, was determined. A relationship between the concentration of fines in the suspension and the structure of the pulp during their sedimentation was established. To intensify the fines sedimentation process, it was proposed to return a part of the sediment to the suspension passing into the physical coagulator. Process parameters for the sedimentation process and the construction of the sedimentation tank were obtained. The unit designed for collecting fines from the suspension is shown schematically. Use of this unit reduced the fibre sedimentation time, decreased the loads in wastewaters, and retained the consumer value of the pulp fibres.